Sagot :
✒️RADIUS
It is given that
- [tex]\tt :\longmapsto\:\vec{r} = a t \: \hat{i} - b {t}^{2} \: \hat{j}[/tex]
So,
On comparing with,
- [tex]\tt :\longmapsto\:\vec{r} = x \: \hat{i} + y \: \hat{j}[/tex]
we get
- [tex]\tt :\implies\:x = at \: \: and \: \: y = - b {t}^{2} [/tex]
Now, eliminate 't' from these two conditions,
- [tex]\tt :\longmapsto\: \: as \: x = at \: \tt :\implies\:t = \dfrac{x}{a} [/tex]
So,
- [tex]\tt :\implies\:y = - b \times \dfrac{ {x}^{2} }{ {a}^{2} } [/tex]
- [tex]\tt :\implies\:y = - \dfrac{b {x}^{2} }{ {a}^{2} } [/tex]
[tex] \underline{\tt \bold{ \: Answer \: (b)}}[/tex]
We know,
- [tex]\tt :\longmapsto\:\vec{v} \: = \: \dfrac{d}{dt} \vec{r}[/tex]
and
- [tex]\tt :\longmapsto\:\vec{w} = \dfrac{d}{dt} \vec{v}[/tex]
As,
- [tex]\tt :\longmapsto\:\vec{r} = a t \: \hat{i} - b {t}^{2} \: \hat{j}[/tex]
On differentiating with respect to 't', we get
- [tex]\tt :\longmapsto\:\dfrac{d}{dr} \vec{r} = \dfrac{d}{dt} (a t \: \hat{i} - b {t}^{2} \: \hat{j})[/tex]
- [tex]\tt :\longmapsto\:\vec{v} = a \: \hat{i} - 2b {t} \: \hat{j}[/tex]
On differentiating with respect to 't', we get
- [tex]\tt :\longmapsto\:\dfrac{d}{dt} \vec{v} = \dfrac{d}{dt} (a\: \hat{i} - 2b {t} \: \hat{j})[/tex]
- [tex]\tt :\longmapsto\:\vec{w} = - 2b \: \hat{j}[/tex]
Now,
- [tex]\tt :\longmapsto\: |\vec{v}| = \sqrt{ {a}^{2} + {( - 2bt)}^{2} } [/tex]
- [tex]\tt\implies \: |\vec{v}| = \sqrt{ {a}^{2} + {4b}^{2} {t}^{2} } [/tex]
And
- [tex]\tt :\longmapsto\: |\vec{w}| = \sqrt{ {( - 2b)}^{2} } [/tex]
- [tex]\tt :\longmapsto\: |\vec{w}| = 2b[/tex]
[tex] \underline{\rm \tt{ \: Answer \: (c)}}[/tex]
We know,
To distinguish the angle 'a' with numeric constant 'a',
Let angle between two vectors be 'p'.
Angle between two vector is given by
- [tex]\tt :\longmapsto\:cosp \: = \dfrac{\vec{v} \: . \: \vec{w}}{ |\vec{v}| \: |\vec{w}| } [/tex]
- [tex]\tt :\longmapsto\:cosp \: = \dfrac{(a\: \hat{i} - 2bt \: \hat{j}) \: . \: ( - 2b \: \hat{j})}{ \sqrt{ {a}^{2} + {4b}^{2} {t}^{2} } \times 2b } [/tex]
- [tex]\tt :\longmapsto\:cosp = \dfrac{ {4tb}^{2} }{ \sqrt{ {a}^{2} + {4b}^{2} {t}^{2} } \times 2b } [/tex]
- [tex]\tt\implies \:cosp = \dfrac{2bt}{ \sqrt{ {a}^{2} + {4b}^{2} {t}^{2} } } [/tex]
As,
We know
- [tex]\tt :\longmapsto\: {tan}^{2} p = {sec}^{2} p - 1[/tex]
- [tex]\tt :\longmapsto\: {tan}^{2} p = \dfrac{ {a}^{2} + 4 {b}^{2} {t}^{2} }{4 {b}^{2} {t}^{2} } - 1[/tex]
- [tex]\tt :\longmapsto\: {tan}^{2} p = \dfrac{ {a}^{2} + 4 {b}^{2} {t}^{2} - 4 {b}^{2} {t}^{2}}{4 {b}^{2} {t}^{2} } [/tex]
- [tex]\tt:\longmapsto\: {tan}^{2} p = \dfrac{ {a}^{2}}{4 {b}^{2} {t}^{2} } [/tex]
- [tex]\tt :\longmapsto\:tanp \: = \: \dfrac{a}{2bt} [/tex]
- [tex]\tt\implies \:p \: = \: {tan}^{ - 1} \bigg(\dfrac{a}{2bt} \bigg)[/tex]
[tex] \underline{\tt \bold{ \: Answer \: (d)}}[/tex]
The mean velocity vector is given by
- [tex]\tt :\longmapsto\:\vec{ \overline{v}} = \dfrac{\int_0^t \: \vec{v} \: dt}{ \int \: dt} [/tex]
- [tex]\tt :\longmapsto\:\vec{ \overline{v}} = \dfrac{\int_0^t \: (a\: \hat{i} - 2bt \: \hat{j}) \: dt}{ t} [/tex]
- [tex]\tt :\longmapsto\:\vec{ \overline{v}} = \dfrac{at\: \hat{i} - 2b \: \dfrac{ {t}^{2} }{2} \: \hat{j} }{t} [/tex]
- [tex]\tt :\longmapsto\:\vec{ \overline{v}} = a\: \hat{i} - b {t} \: \hat{j}[/tex]
Hence,
- [tex]\tt :\longmapsto\: |\vec{ \overline{v}} | = \sqrt{ {a}^{2} + {( - bt)}^{2} } [/tex]
- [tex]\tt\implies \: |\vec{ \overline{v}}| = \sqrt{ {a}^{2} + {b}^{2} {t}^{2} } [/tex]
#CarryOnLearning
[tex]\qquad\qquad\qquad\qquad\qquad\qquad\tt{fri \: 03-04-2022} \\ \qquad\qquad\qquad\qquad\qquad\qquad\tt{11:44 \: am}[/tex]